Personajes y escenarios: motivos compartidos en "Don Quijote" y "La pícara Justina" - Rodríguez, Adriana Azucena (El Colegio de México, 2016)
This article compares the way that several motifs and topics are presented in El ingenioso hidalgo don Quijote de la Mancha with the way they are developed in La pícara Justina. Both novels were published in 1605, in the “academic” context of the day. At the time the term “academy” indicated a group of intellectuals gathered around common cultural interests. The purpose of this paper is to highlight the characters, situations, and scenarios shared by both novels. Thoughts on intertextuality, are offered in the course of a commentary on the similarities and differences between two works, published in the same social and geographical world, and above all, in similar literary and academic contexts.